(untitled) (Tempo e Argumento, 2020)
The purpose of this text is to reflect about the mechanisms of graphic humor produced between the impeachment of Dilma Rousseff, who was removed from office in 2016, and the end of Michel Temer’s government in December 2018. During the survey of the strips of the section Cartoons / Daily Cartoons of Folha de S. Paulo, from December 2015 to the end of 2018, it was possible to observe positions contrary to the coup, challenging the alleged neutrality of the journal. The mixture of elements from the cartoon and the comics gave rise to a hybrid product that sought to explain, laugh and criticize the unusual situations that followed in the fearful national panorama. For this article, only the strips made by women were considered, specifically the comics by Thaïs Gualberto and Fabiane Langona. The idea is to think about the way in which the characters created by these two cartoonists dialogued with feminist issues and the women’s agendas of struggle, in the midst of a coup. Strips with themes on the characterizations of the Temer government, the view on Brazil and the politics marked by the electoral campaign and the presidential election of 2018 were analyzed, taking into account the choices of resources and technical procedures that caused the humorous effect. In interpreting the events of the impeachment and the Temer government, the comic artists sought inspiration in the news, in the daily life of cities and in personal experiences, constructing other narratives, from the point of view of women’s struggles and resistance practices. Keywords: Thaïs Gualberto. Fabiane Langona. Graphic Humor. Comics.